Low-copper high-iron copper alloy and production method thereof

By adjusting the composition and process design of copper alloys and optimizing the microstructure of recycled brass alloys, the problem of poor mechanical performance of high-speed iron alloys is solved, and the processing performance and mechanical performance is improved, which is suitable for a variety of application scenarios.

CN119220852APending Publication Date: 2024-12-31NINGBO CHANGZHEN COPPER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411233241.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The high impurity content and lots of slag inclusions in recycled brass alloys lead to low mechanical properties, especially the high iron content, which leads to the formation of dendritic iron-based solid solution, weak peeling interface, affecting tensile properties.

Method used

By adjusting the copper alloy composition, Cu 52-56 wt%, Pb 2.0-4.0 wt%, Ni 0.3-0.6 wt%, Fe 0.8-1.5 wt%, Sn 0.5-0.8 wt%, Mn ≤1.0 wt%, Al ≤0.1 wt %, control the microstructure of coexistence of β-phase matrix, α-phase and lead-rich phase, and coordinate elements such as iron, tin, nickel, manganese, optimize process design, avoid the enrichment of iron and lead, and improve strength and corrosion resistance.

Benefits of technology

It has achieved low-copper high-speed copper alloys with good processing plasticity, excellent turning performance, golden surface gloss and improved mechanical properties, extending service life and reducing production costs. It is suitable for non-direct drinking, edible scenarios and ornamental crafts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220852A_ABST
    Figure CN119220852A_ABST
Patent Text Reader

Abstract

The invention relates to the field of alloys, and provides a low-copper high-iron copper alloy and a production method thereof for solving the problem of poor mechanical performance of a low-copper high-iron alloy, the copper alloy comprises 52-56 wt% of Cu, 2.0-4.0 wt% of Pb, 0.3-0.6 wt% of Ni, 0.8-1.5 wt% of Fe, 0.5-0.8 wt% of Sn, less than or equal to 1.0 wt% of Mn, less than or equal to 0.1 wt% of Al, less than or equal to 0.6 wt% of inevitable impurity elements and the balance of Zn; the sum of the weight percentages of all the elements is 100 wt%. Regenerated brass and brass machining scraps are used as main raw materials for melting and ingot casting production, and the low-copper and high-iron copper alloy which is good in machining plasticity, excellent in turning machining performance, golden yellow in surface gloss and good in mechanical performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of alloys, in particular to a low-copper and high-iron copper alloy and a production method thereof. Background Art

[0002] Copper and copper alloys have good chemical stability and low-temperature oxidation resistance. Their quality and composition change very little during service. Through technical processing, they can be converted into renewable resources for recycling, thereby reducing dependence on primary ore. The main sources of recycled copper raw materials include scrapped copper-containing scrap parts, waste from the production of copper, copper alloys and their mechanical processing, copper slag and smoke collected during the smelting process. After the scrap copper is recycled and disassembled, the copper waste is strictly classified and then recycled in a targeted manner. Among them, high-grade pure copper materials can be used directly and returned for reprocessing, and the remaining low-purity waste can be used to produce recycled refined copper or directly smelted into copper alloys.

[0003] Copper alloys have medium strength, are easy to process, are relatively resistant to fatigue, have beautiful colors, and have good electrical conductivity, thermal conductivity, and corrosion resistance, and are widely used. Recycled brass is one of the common recycled coppers. When most or all of the raw materials are scrap brass, the recycled brass alloy has high impurity content, many inclusions, and common slag inclusions. In addition, the prepared brass alloy has a high iron content, which is difficult to lower. The high iron content in the brass alloy is prone to forming dendritic iron-based solid solutions. The interface between the iron-based dendrites and the matrix is ​​a weak link. During the brass stretching process, the brass matrix is ​​easily peeled off from the interface, which is one of the main reasons for the low mechanical properties of recycled brass. Therefore, additional treatment is required to improve the mechanical properties of recycled brass. For example, patent CN102168193A discloses a method for regenerating and continuously casting high-quality brass alloy from waste brass. After the existing technology - smelting, refining, and adjusting the alloy composition, 0.05-3.00% of the weight of the alloy melt is added to the waste rare earth cobalt permanent magnet material, and then the slag on the surface of the melt is removed before casting. The tensile strength and elongation of the resulting brass alloy are improved by more than 20% compared with the performance of the brass alloy prepared by the existing technology. Summary of the invention

[0004] In order to overcome the problem of poor mechanical properties of low-copper and high-iron alloys, the present invention provides a low-copper and high-iron copper alloy and a production method thereof. By adjusting the components and their contents, a low-copper and high-iron copper alloy with good processing plasticity, excellent turning performance, a golden surface luster and good mechanical properties is obtained.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A low-copper and high-iron copper alloy, comprising: Cu 52-56wt%, Pb 2.0-4.0wt%, Ni 0.3-0.6wt%, Fe0.8-1.5wt%, Sn 0.5-0.8wt%, Mn≤1.0wt%, Al≤0.1wt%, inevitable impurity elements≤0.6wt%, and the balance is Zn; the sum of the weight percentages of each element is 100wt%, and the inevitable impurity elements include one or more of Sb, P, As, Si, S, Mg, and Te.

[0006] The copper alloy has a microstructure in which a β phase matrix, an α phase and a lead-rich phase coexist, and part of the α phase precipitates around the lead-rich phase. The present invention controls the alloy structure to the α+β phase, reduces the copper content as much as possible, and optimizes the performance through alloy and process design. The functions of each element are as follows: (1) Iron as an "artificial crystal nucleus" can refine the grains, and combined with tin and nickel can improve the strength and corrosion resistance of the alloy. The increase of iron can also effectively reduce the production cost, but it is necessary to avoid the enrichment of iron and lead through alloy composition adjustment and process design.

[0007] (2) Tin can effectively inhibit dezincification, and when combined with iron, it can improve the strength and corrosion resistance of the alloy. This alloy is a high-zinc alloy. In order to achieve the purpose of anti-dezincification and corrosion resistance, the tin content should be controlled at 0.5-0.7wt%. If the tin content is lower than 0.5wt%, the anti-dezincification and corrosion resistance effects are not obvious; when the tin content is higher than 0.7wt%, it will greatly promote the enrichment of iron, resulting in poor alloy performance. In addition, tin is the most common alloying element in recycled copper alloy raw materials, and tin in brass is an element that is difficult to remove at low cost. The present invention efficiently utilizes the Sn element, which is widely available and difficult to remove in scrap copper.

[0008] (3) Lead is the most common element in recycled lead brass. The cost of recycling it alone is relatively high, and recycling is obviously a better solution. After years of development, its recycling has become very mature, especially for the guarantee of cutting performance and homogenization of recycled raw materials, which are better than original materials.

[0009] (4) Nickel can promote the precipitation of α phase, improve the strength, toughness and corrosion resistance of the alloy, and at the same time, nickel can inhibit the precipitation of iron and reduce the risk of agglomeration and enrichment of elemental iron. When the iron content is high, when the nickel content is higher than 0.3%, it has good plasticity. When the nickel content reaches 0.6%, the plasticity of brass increases significantly. In addition, when the nickel content exceeds a certain amount, the color of the alloy turns white. Considering that the amount of raw materials containing nickel-containing recycled copper alloy with complex composition is relatively small, the nickel content after proportioning is below 0.6%, which is the most suitable cost.

[0010] (5) Manganese can significantly improve the corrosion resistance of brass in seawater, chlorides and superheated steam, improve the strength of the alloy, and at the same time increase the solubility of iron in the melt and reduce the total amount of iron-rich phase precipitation.

[0011] (6) Aluminum can disperse the distribution of precipitated phases and reduce the size of precipitated phases, thereby improving iron enrichment. However, the aluminum source used in the present invention is recycled aluminum and aluminum bronze recycled materials, which contain impurity zinc. Increasing the amount of zinc will greatly increase the proportion of β phase, and the addition amount and usage scenario need to be strictly controlled. The present invention strictly controls the aluminum content in the alloy to not exceed 0.1wt%, and the usage scenario is preferably a rod.

[0012] Preferably, the content of the inevitable impurity element Si in the alloy does not exceed 0.02wt%. Silicon will react with iron to form high-hardness particles, which will deteriorate the cold working performance of the alloy. Therefore, the alloy of the present invention strictly controls the silicon content in the alloy to not exceed 0.02wt%.

[0013] Preferably, the copper alloy with low copper and high iron has a composition of Cu 54-56wt%, Pb 2.0-4.0wt%, Ni 0.3-0.6wt%, Fe 0.8-1.5wt%, Sn 0.5-0.7wt%, Mn≤0.1wt%, Al≤0.1wt%, unavoidable impurity elements≤0.2wt%, and the balance is Zn.

[0014] The present invention also provides a method for producing the low-copper and high-iron copper alloy, comprising the following steps: (1) Ingredients: Recycled brass and brass processing scraps are used as main raw materials, and Cu source, Pb source, Ni source, Fe source, Sn source, Al source and Zn source are added; (2) The raw materials are melted to produce ingots.

[0015] Preferably, the recycled brass accounts for 10-30wt% of the total weight of the raw materials, and the brass processing scraps account for no less than 50wt% of the total weight of the raw materials.

[0016] Preferably, the Cu source is recycled copper, the Pb source is recycled lead, the Ni source is one or both of white copper recycled material and nickel-plated recycled brass material, the Fe source is one or both of copper-iron alloy and iron powder, the Sn source is one or both of tin bronze recycled material and tin-plated recycled brass material, the Al source is one or both of recycled aluminum and aluminum bronze recycled material, and the Zn source is recycled zinc.

[0017] Preferably, the melting step is specifically as follows: adding the raw materials into the smelting furnace and melting them under high pressure until flame spraying occurs, adding a slag cleaning agent under low pressure after flame spraying, taking samples after stirring for pre-furnace component analysis, if the components are unqualified, adjusting the components to qualified ones, removing the slag, and discharging the slag into the casting furnace.

[0018] Preferably, horizontal continuous casting is used to produce the ingots.

[0019] Preferably, the ingot is cut into extruded ingots, and extruded at 600-680°C to obtain rods with a diameter of 6-15 mm.

[0020] Therefore, the beneficial effects of the present invention are: (1) under the condition of reduced copper content, the α phase content in its microstructure is higher than the theoretical value, ensuring that it has good low-temperature processing performance; (2) While ensuring the turning performance, the copper alloy has improved resistance to dezincification, stress corrosion, oxidation and stability, ensuring its longer service life; (3) The copper alloy has a golden appearance and oxidation resistance, which gives it a better color and life, and can be displayed or used as a handicraft; (4) Copper alloys have excellent hot working properties. This property can be used to obtain special profiles through extrusion, hot forging, hot stamping and machining, and the cost is relatively low; (5) The production cost of copper alloy is very low. Its production uses recycled copper alloy as the main raw material. By utilizing the interaction of elements, the role of the alloy elements in the recycled raw materials can be fully exerted, which significantly improves the value of the raw materials. The alloy can be used in non-direct drinking and eating scenarios, occasions where there is no or little contact with the human body, ornamental handicrafts, and architectural structures that are both functional and decorative. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a diagram showing the organizational structure of the copper alloy of Example 1.

[0022] Figure 2 Schematic diagram of the rod obtained by the present invention.

[0023] Figure 3 This is a comparison chart of the effect of iron content on the metallographic structure of copper alloy.

[0024] Figure 4 This is a comparison chart of the effect of manganese on the metallographic structure of copper alloy.

[0025] Figure 5 This is a comparison chart of the effect of nickel on the metallographic structure of copper alloy.

[0026] Figure 6 This is a comparison chart of the effect of tin on the metallographic structure of copper alloy. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further described below through specific embodiments.

[0028] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are all weight parts, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.

[0029] Example A low-copper and high-iron copper alloy, comprising: Cu 52-56wt%, Pb 2.0-4.0wt%, Ni 0.3-0.6wt%, Fe0.8-1.5wt%, Sn 0.5-0.8wt%, Mn≤1.0wt%, Al≤0.1wt%, inevitable impurity elements≤0.6wt%, and the balance is Zn; the sum of the weight percentages of each element is 100wt%, and the inevitable impurity elements include one or more of Sb, P, As, Si, S, Mg, and Te.

[0030] Further preferred is: Cu 54-56wt%, Pb 2.0-4.0wt%, Ni 0.3-0.6wt%, Fe 0.8-1.5wt%, Sn0.5-0.7wt%, Mn≤0.1wt%, Al≤0.1wt%, inevitable impurity elements≤0.2wt%, and the balance is Zn; the sum of the weight percentages of each element is 100wt%, and the inevitable impurity elements include one or more of Sb, P, As, Si, S, Mg, and Te, and Si≤0.02wt%.

[0031] The copper alloy has a microstructure in which a β phase matrix, an α phase and a lead-rich phase coexist, and part of the α phase precipitates around the lead-rich phase. The present invention controls the alloy structure to the α+β phase, reduces the copper content as much as possible, and optimizes the performance through alloy and process design.

[0032] The present invention also provides a method for producing the low-copper and high-iron copper alloy, comprising the following steps: (1) Ingredients: Recycled brass and brass processing scraps are used as the main raw materials, with recycled brass accounting for 10-30wt% of the total raw materials, and brass processing scraps not less than 50wt% of the total raw materials; Cu source, Pb source, Ni source, Fe source, Sn source, Al source and Zn source are added; the Cu source is recycled copper, the Pb source is recycled lead, the Ni source is one or two of white copper recycled material and nickel-plated recycled brass material, the Fe source is one or two of copper-iron alloy and iron powder, the Sn source is one or two of tin bronze recycled material and tin-plated recycled brass material, the Al source is one or two of recycled aluminum and aluminum bronze recycled material, and the Zn source is recycled zinc. Recycled aluminum and aluminum bronze recycled materials: the proportion is calculated based on the target content balance of Al in the alloy.

[0033] The raw materials are pre-processed: large pieces, high value-added pieces, stainless steel, and plastics are manually selected from recycled brass, and iron products are magnetically selected. After crushing, magnetic separation and panning are performed to remove free iron and non-metallic inclusions, ash, etc., and the raw materials are fully mixed. 5-10 kg of representative samples are added to the crucible, heated and melted, slag is removed, and chemical composition samples are taken. The composition analysis and discount rate calculation are completed. Repeat 3 groups. If the difference is large, the number of experiments can be increased. After passing the test, they will be put aside for use. Recycled copper, recycled brass, recycled zinc, recycled aluminum, recycled lead, copper-iron alloy, iron powder, brass processing chips, recycled aluminum bronze, recycled tin bronze, recycled white copper, nickel-plated recycled brass, tin-plated recycled brass and other recycled copper raw materials are tested for composition through handheld spectroscopy, titration and other means, and the results are summarized for subsequent calculation and use.

[0034] (2) Melting: The raw materials are put into the industrial frequency induction melting furnace and melted under high pressure until the flame is sprayed. To accelerate the melting process, a pressing device is used to press the raw materials into the copper water and cover the surface of the copper water to reduce heat loss. Mechanical stirring is interspersed during the melting process. At the same time, flux can be added to accelerate melting and reduce the adverse effects of oil and water. After the flame is sprayed, low pressure insulation is added with slag cleaning agent. After stirring for 3-5 minutes, samples are taken for pre-furnace component analysis. If the composition is unqualified, the composition is adjusted to qualified, and the slag is removed and discharged to the insulation (casting) furnace.

[0035] (3) Ingot casting: Ingot casting is produced by horizontal continuous casting. The ingot pulled out after electromagnetic stirring is cut into extruded ingots by sawing machine. The finished products are φ15mm and φ6mm. The extrusion temperatures are designed to be 600-620℃ and 660-680℃ respectively according to the extrusion ratio. After the extruded rod billet is headed, it is subjected to subsequent surface peeling, stretching and sizing, straightening, and low-temperature annealing on the straight drawing machine to obtain φ15mm rods; after the extruded wire billet is jointed, it is subjected to finishing and shrinking on the wire drawing machine, and recrystallization in the annealing furnace, and then peeling, stretching, shearing, and polishing on the drawing machine to obtain φ6mm finished products. Among them, φ15mm rods can be processed separately.

[0036] The ingot is sawn into extrusion billets, and large extrusion billets are produced by extrusion machines. Extrusion billets are obtained by extrusion and processed to obtain products; or the melt is poured into a prefabricated product model and the product is obtained by lost wax casting. The extruded rod can be headed and then subjected to subsequent surface peeling or stretching and sizing, stress relief annealing on a straight drawing machine, or surface turning and straightening to produce round bars. The deformed bars can be hot-forged to produce door handles, lamp holders, corner pages and other products. Extruded rods can also be directly hot-extruded into profile products, such as building roofing materials, high-end window frames, floor strips and other functional and ornamental building components. The extruded wire can be spliced ​​and then subjected to subsequent surface peeling or stretching and sizing on a coil drawing car, recrystallization annealing, and then coiled wire or straight bars can be produced by a coil drawing car or drawing machine; the extruded wire can be spliced ​​and then directly produced by a drawing machine; and then various products can be made by subsequent turning, punching, hot forging, electroplating, etc. Cast products can be obtained by lost wax casting, such as various ornamental artworks and decorative pieces.

[0037] Example 1 A low-copper and high-iron copper alloy, comprising: Cu 52.37wt%, Pb 2.31wt%, Ni 0.55wt%, Fe 0.93wt%, Sn 0.63wt%, Mn 0.56wt%, Al 0.013wt%, unavoidable impurity elements ≤ 0.6wt% (including Sb, P, As, Si, S, Mg, Te, wherein Si 0.0038wt%), and the balance Zn; the sum of the weight percentages of the elements is 100wt%. Figure 1 It can be seen that the alloy of the present invention has a microstructure in which a β phase matrix, an α phase and a lead-rich phase coexist, and part of the α phase precipitates around the lead-rich phase.

[0038] The preparation method of the copper alloy with low copper and high iron is as follows: (1) Raw material pretreatment Recycled brass is manually sorted out for large pieces, high value-added pieces, stainless steel, and plastics, and iron products are magnetically sorted out. After crushing, magnetic separation and panning are performed to remove free iron and non-metallic inclusions, ash, etc., and fully mixed. 5-10 kg of representative samples are added to the crucible, heated to melt, slag removed, and chemical composition samples are taken. The composition analysis and discount rate calculation are completed. Repeat 3 groups. If the difference is large, the number of experiments can be increased. After passing the test, they are set aside for use. Recycled copper, recycled brass, recycled zinc, recycled aluminum, recycled lead, copper-iron alloy, iron powder, brass processing chips, recycled aluminum bronze, recycled tin bronze, recycled white copper, nickel-plated recycled brass, tin-plated recycled brass and other recycled copper raw materials are tested for their components through handheld spectroscopy and titration, and the results are summarized and awaiting subsequent use in blending.

[0039] (2) Ingredients Recycled brass: 20wt% of the total weight of raw materials; Brass processing scraps: 50wt% of the total weight of raw materials; Recycled aluminum and aluminum bronze recycled materials: the proportion is calculated based on the target content of Al in the alloy; White copper recycled material, nickel-plated recycled brass material: the proportion is calculated based on the target content of Ni in the alloy; Tin bronze recycled material, tin-plated recycled brass material: the proportion is calculated based on the target content of Sn in the alloy; Recycled copper: The proportion is calculated based on the target content of Cu in the alloy; Recycled zinc: The proportion is calculated based on the target content balance of Zn in the alloy; Recycled lead: The proportion is calculated based on the target content of Pb in the alloy; Copper-iron alloy, iron powder: The proportion is calculated based on the target content of Fe in the alloy.

[0040] Among them, Mn and Si exist in small amounts in recycled brass and brass processing chips.

[0041] (3) Melting The above raw materials are put into the industrial frequency induction melting furnace respectively, and melted under high pressure until the flame is sprayed. In order to accelerate the melting process, the raw materials are pressed into the copper water by the pressing equipment, and the surface of the copper water is covered to reduce heat loss, and mechanical stirring is interspersed. After the flame is sprayed, low pressure insulation is added with slag cleaning agent, and after stirring for 4 minutes, samples are taken for pre-furnace component analysis. If the composition is unqualified, the composition is adjusted to qualified, and the slag is removed and discharged to the insulation (casting) furnace.

[0042] (4) Ingot The ingots are produced by horizontal continuous casting. The ingots pulled out after electromagnetic stirring are cut into extruded billets by sawing machine. The finished product is φ15mm. The extrusion temperature is designed to be 620℃ according to the extrusion ratio. After the extruded billet is headed, the subsequent surface peeling, stretching and sizing, straightening and low-temperature annealing are carried out on the straight drawing machine to obtain φ15mm bars. Figure 2 As shown, the rod is a lustrous golden yellow.

[0043] Example 2 A low-copper and high-iron copper alloy comprises: 53.15wt% Cu, 2.64wt% Pb, 0.56wt% Ni, 1.08wt% Fe, 0.66wt% Sn, 0.62wt% Mn, Al<0.001wt%, inevitable impurity elements ≤0.6wt% (including Sb, P, As, Si, S, Mg, Te, wherein Si is 0.0031wt%), and the balance is Zn; the sum of the weight percentages of the elements is 100wt%.

[0044] The preparation method of the copper alloy with low copper and high iron is as follows: (1) Raw material pretreatment Recycled brass is manually sorted out for large pieces, high value-added pieces, stainless steel, and plastics, and iron products are magnetically sorted out. After crushing, magnetic separation and panning are performed to remove free iron and non-metallic inclusions, ash, etc., and fully mixed. 5-10 kg of representative samples are added to the crucible, heated to melt, slag removed, and chemical composition samples are taken. The composition analysis and discount rate calculation are completed. Repeat 3 groups. If the difference is large, the number of experiments can be increased. After passing the test, they are set aside for use. Recycled copper, recycled brass, recycled zinc, recycled aluminum, recycled lead, copper-iron alloy, iron powder, brass processing chips, recycled aluminum bronze, recycled tin bronze, recycled white copper, nickel-plated recycled brass, tin-plated recycled brass and other recycled copper raw materials are tested for their components through handheld spectroscopy and titration, and the results are summarized and awaiting subsequent use in blending.

[0045] (2) Ingredients Recycled brass: 20wt% of the total weight of raw materials; Brass processing scraps: 50wt% of the total weight of raw materials; Recycled aluminum and aluminum bronze recycled materials: the proportion is calculated based on the target content of Al in the alloy; White copper recycled material, nickel-plated recycled brass material: the proportion is calculated based on the target content of Ni in the alloy; Tin bronze recycled material, tin-plated recycled brass material: the proportion is calculated based on the target content of Sn in the alloy; Recycled copper: The proportion is calculated based on the target content of Cu in the alloy; Recycled zinc: The proportion is calculated based on the target content balance of Zn in the alloy; Recycled lead: The proportion is calculated based on the target content of Pb in the alloy; Copper-iron alloy, iron powder: The proportion is calculated based on the target content of Fe in the alloy.

[0046] Among them, Mn and Si exist in small amounts in recycled brass and brass processing chips.

[0047] (3) Melting The above raw materials are put into the industrial frequency induction melting furnace respectively, and melted under high pressure until the flame is sprayed. In order to accelerate the melting process, the raw materials are pressed into the copper water by the pressing equipment, and the surface of the copper water is covered to reduce heat loss, and mechanical stirring is interspersed. After the flame is sprayed, low pressure insulation is added with slag cleaning agent, and after stirring for 4 minutes, samples are taken for pre-furnace component analysis. If the composition is unqualified, the composition is adjusted to qualified, and the slag is removed and discharged to the insulation (casting) furnace.

[0048] (4) Ingot The ingots are produced by horizontal continuous casting. The ingots pulled out after electromagnetic stirring are cut into extruded ingots by sawing machines. The finished product is φ15mm. The extrusion temperature is designed to be 620℃ according to the extrusion ratio. After the extruded extruded bar billet is headed, the subsequent surface peeling, stretching and sizing, straightening, and low-temperature annealing are carried out on the straight drawing machine to obtain φ15mm bars.

[0049] Example 3 A low-copper and high-iron copper alloy comprises: 54.64wt% Cu, 3.15wt% Pb, 0.35wt% Ni, 1.26wt% Fe, 0.54wt% Sn, 0.75wt% Mn, 0.015wt% Al, inevitable impurity elements ≤0.6wt% (including Sb, P, As, Si, S, Mg, Te, wherein Si is 0.0022wt%), and the balance is Zn; the sum of the weight percentages of the elements is 100wt%.

[0050] The preparation method of the copper alloy with low copper and high iron is as follows: (1) Raw material pretreatment Recycled brass is manually sorted out for large pieces, high value-added pieces, stainless steel, and plastics, and iron products are magnetically sorted out. After crushing, magnetic separation and panning are performed to remove free iron and non-metallic inclusions, ash, etc., and fully mixed. 5-10 kg of representative samples are added to the crucible, heated to melt, slag removed, and chemical composition samples are taken. The composition analysis and discount rate calculation are completed. Repeat 3 groups. If the difference is large, the number of experiments can be increased. After passing the test, they are set aside for use. Recycled copper, recycled brass, recycled zinc, recycled aluminum, recycled lead, copper-iron alloy, iron powder, brass processing chips, recycled aluminum bronze, recycled tin bronze, recycled white copper, nickel-plated recycled brass, tin-plated recycled brass and other recycled copper raw materials are tested for their components through handheld spectroscopy and titration, and the results are summarized and awaiting subsequent use in blending.

[0051] (2) Ingredients Recycled brass: 20wt% of the total weight of raw materials; Brass processing scraps: 50wt% of the total weight of raw materials; Recycled aluminum and aluminum bronze recycled materials: the proportion is calculated based on the target content of Al in the alloy; White copper recycled material, nickel-plated recycled brass material: the proportion is calculated based on the target content of Ni in the alloy; Tin bronze recycled material, tin-plated recycled brass material: the proportion is calculated based on the target content of Sn in the alloy; Recycled copper: The proportion is calculated based on the target content of Cu in the alloy; Recycled zinc: The proportion is calculated based on the target content balance of Zn in the alloy; Recycled lead: The proportion is calculated based on the target content of Pb in the alloy; Copper-iron alloy, iron powder: The proportion is calculated based on the target content of Fe in the alloy.

[0052] Among them, Mn and Si exist in small amounts in recycled brass and brass processing chips.

[0053] (3) Melting The above raw materials are put into the industrial frequency induction melting furnace respectively, and melted under high pressure until the flame is sprayed. In order to accelerate the melting process, the raw materials are pressed into the copper water by the pressing equipment, and the surface of the copper water is covered to reduce heat loss, and mechanical stirring is interspersed. After the flame is sprayed, low pressure insulation is added with slag cleaning agent, and after stirring for 4 minutes, samples are taken for pre-furnace component analysis. If the composition is unqualified, the composition is adjusted to qualified, and the slag is removed and discharged to the insulation (casting) furnace.

[0054] (4) Ingot The ingots are produced by horizontal continuous casting. The ingots pulled out after electromagnetic stirring are cut into extruded ingots by sawing machines. The finished product is φ15mm. The extrusion temperature is designed to be 620℃ according to the extrusion ratio. After the extruded extruded bar billet is headed, the subsequent surface peeling, stretching and sizing, straightening, and low-temperature annealing are carried out on the straight drawing machine to obtain φ15mm bars.

[0055] Example 4 A low-copper and high-iron copper alloy comprises: 55.71wt% Cu, 3.65wt% Pb, 0.58wt% Ni, 1.42wt% Fe, 0.54wt% Sn, 1.03wt% Mn, 0.015wt% Al, inevitable impurity elements ≤0.6wt% (including Sb, P, As, Si, S, Mg, Te, wherein Si is 0.001wt%), and the balance is Zn; the sum of the weight percentages of the elements is 100wt%.

[0056] The preparation method of the copper alloy with low copper and high iron is as follows: (1) Raw material pretreatment Recycled brass is manually sorted out for large pieces, high value-added pieces, stainless steel, and plastics, and iron products are magnetically sorted out. After crushing, magnetic separation and panning are performed to remove free iron and non-metallic inclusions, ash, etc., and fully mixed. 5-10 kg of representative samples are added to the crucible, heated to melt, slag removed, and chemical composition samples are taken. The composition analysis and discount rate calculation are completed. Repeat 3 groups. If the difference is large, the number of experiments can be increased. After passing the test, they are set aside for use. Recycled copper, recycled brass, recycled zinc, recycled aluminum, recycled lead, copper-iron alloy, iron powder, brass processing chips, recycled aluminum bronze, recycled tin bronze, recycled white copper, nickel-plated recycled brass, tin-plated recycled brass and other recycled copper raw materials are tested for their components through handheld spectroscopy and titration, and the results are summarized and awaiting subsequent use in blending.

[0057] (2) Ingredients Recycled brass: 20wt% of the total weight of raw materials; Brass processing scraps: 50wt% of the total weight of raw materials; Recycled aluminum and aluminum bronze recycled materials: the proportion is calculated based on the target content of Al in the alloy; White copper recycled material, nickel-plated recycled brass material: the proportion is calculated based on the target content of Ni in the alloy; Tin bronze recycled material, tin-plated recycled brass material: the proportion is calculated based on the target content of Sn in the alloy; Recycled copper: The proportion is calculated based on the target content of Cu in the alloy; Recycled zinc: The proportion is calculated based on the target content balance of Zn in the alloy; Recycled lead: The proportion is calculated based on the target content of Pb in the alloy; Copper-iron alloy, iron powder: The proportion is calculated based on the target content of Fe in the alloy.

[0058] Among them, Mn and Si exist in small amounts in recycled brass and brass processing chips.

[0059] (3) Melting The above raw materials are put into the industrial frequency induction melting furnace respectively, and melted under high pressure until the flame is sprayed. In order to accelerate the melting process, the raw materials are pressed into the copper water by the pressing equipment, and the surface of the copper water is covered to reduce heat loss, and mechanical stirring is interspersed. After the flame is sprayed, low pressure insulation is added with slag cleaning agent, and after stirring for 4 minutes, samples are taken for pre-furnace component analysis. If the composition is unqualified, the composition is adjusted to qualified, and the slag is removed and discharged to the insulation (casting) furnace.

[0060] (4) Ingot The ingots are produced by horizontal continuous casting. The ingots pulled out after electromagnetic stirring are cut into extruded ingots by sawing machines. The finished product is φ15mm. The extrusion temperature is designed to be 620℃ according to the extrusion ratio. After the extruded extruded bar billet is headed, the subsequent surface peeling, stretching and sizing, straightening, and low-temperature annealing are carried out on the straight drawing machine to obtain φ15mm bars.

[0061] Comparative Example 1 A brass alloy comprises: 57.68wt% of Cu, 2.64wt% of Pb, 0.16wt% of Ni, 0.31wt% of Fe, 0.45wt% of Sn, less than 0.001wt% of Mn, 0.02wt% of Al, and unavoidable impurity elements of ≤0.6wt% (including Sb, P, As, Si, S, Mg, Te, wherein Si is 0.0078wt%), and the balance is Zn; the sum of the weight percentages of the elements is 100wt%.

[0062] The preparation method of the brass alloy is the same as that of Example 1.

[0063] Comparative Example 2 A brass alloy comprises: 58.46wt% of Cu, 3.13wt% of Pb, 0.21wt% of Ni, 0.33wt% of Fe, 0.41wt% of Sn, less than 0.001wt% of Mn, 0.013wt% of Al, ≤0.6wt% of inevitable impurity elements (including Sb, P, As, Si, S, Mg, Te, wherein Si is 0.0085wt%), and the balance is Zn; the sum of the weight percentages of the elements is 100wt%.

[0064] The preparation method of the brass alloy is the same as that of Example 1.

[0065] Comparative Example 3 The difference from Example 1 is that the iron content is too high, 2 wt %; the sum of the copper and iron contents remains roughly unchanged.

[0066] Comparative Example 4 The difference from Example 1 is that the manganese content is too low, 0.2 wt %; and the sum of the copper and manganese contents remains roughly unchanged.

[0067] Comparative Example 5 The difference from Example 1 is that the nickel content is too low, which is 0.2 wt %; and the sum of the copper and nickel contents remains roughly unchanged.

[0068] Comparative Example 6 The difference from Example 1 is that the tin content is too high, 0.9 wt %; and the sum of the copper and tin contents remains roughly unchanged.

[0069] Comparative Example 7 The difference from Example 1 is that the tin content is too high, 0.4 wt %; and the sum of the contents of copper and tin remains roughly unchanged.

[0070] Performance Testing The rods prepared in the above embodiments and comparative examples were subjected to performance tests in accordance with GB / T 37569-2019 Copper Alloy Rods for Hot Die Forging, and the results are shown in the following table.

[0071] It can be seen from the above table that the low-copper and high-iron bars prepared in Examples 1-4 of the present invention have mechanical properties that are not lower than those of the ordinary brass bars in Comparative Examples 1 and 2, indicating that the present invention does overcome the disadvantages of low-copper and high-iron alloys by blending components, and that low-copper and high-iron alloys can significantly reduce costs.

[0072] Compared with Example 1: (1) The iron content in Example 3 is too high. Iron can act as an "artificial crystal nucleus" to refine the grains, and can improve the strength and corrosion resistance of the alloy when combined with tin and nickel. The increase in iron can also effectively reduce production costs, but it is necessary to avoid the enrichment of iron and lead through alloy composition adjustment and process design. Excessive iron content can easily form dendritic iron-based solid solutions. The interface between the iron-based dendrites and the matrix is ​​a weak link. During the alloy stretching process, the brass matrix is ​​easily peeled off from the interface, resulting in lower mechanical properties. Figure 3 As shown in the circle, when the iron content is within the reasonable range of the present invention, the two-dimensional morphology of the iron precipitate phase is clover-like, and when it exceeds the preferred range of the present invention, the iron-rich precipitate phase shows obvious segregation in the matrix. Therefore, even if the present invention can increase the iron content, it is still necessary to control the iron content within a reasonable range so that it can be compensated by the combination of other elements, and it cannot be increased excessively.

[0073] (2) The manganese content in Comparative Example 4 is lower than the preferred range. Manganese can increase the solubility of iron in the melt and reduce the total amount of iron-rich phase precipitation. Figure 4 As shown, when other conditions remain unchanged, the manganese content is reduced and the iron phase precipitates.

[0074] (3) The nickel content in comparative example 5 is relatively low. Nickel can promote the precipitation of the α phase, improve the strength and toughness of the alloy, and at the same time, nickel can inhibit the precipitation of iron, reducing the risk of agglomeration and enrichment of elemental iron. Figure 5 As shown. When the iron content is high, the nickel content is 0.4%, and the plasticity is good. When the nickel content is 0.6%, the plasticity of brass increases significantly. In addition, when the nickel content exceeds a certain amount, the color of the alloy turns white. Considering that the amount of nickel-containing recycled copper alloy raw materials with complex components is relatively small, the nickel content after proportioning is below 0.6%, which is the most suitable cost.

[0075] (4) The tin content of Comparative Examples 6 and 7 is not within the preferred range. Tin can effectively inhibit dezincification, and when combined with iron, it can improve the strength and corrosion resistance of the alloy. The alloy of the present invention is a high-zinc alloy. In order to achieve the purpose of anti-dezincification and corrosion resistance, the tin content should be controlled at 0.5-0.7wt%. If the tin content is lower than 0.5wt%, the anti-dezincification and corrosion resistance effects are not obvious; when the tin content is higher than 0.7wt%, such as Figure 6 As shown, it will greatly promote the enrichment of iron, resulting in poor alloy performance. In addition, tin is the most common alloying element in the recycled copper alloy raw material, and tin in brass is an element that is difficult to remove at low cost. The present invention efficiently utilizes the Sn element in scrap copper, which has a wide source and is difficult to remove.

[0076] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A copper alloy with low copper content and high iron content, characterized in that: The composition is: Cu 52-56wt%, Pb 2.0-4.0wt%, Ni 0.3-0.6wt%, Fe 0.8-1.5wt%, Sn 0.5-0.8wt%, Mn ≤ 1.0wt%, Al ≤ 0.1wt%, unavoidable impurity elements ≤ 0.6wt%, and the balance is Zn; the sum of the weight percentages of each element is 100wt%.

2. The low-copper and high-iron copper alloy according to claim 1, characterized in that: The composition is: Cu 54-56wt%, Pb2.0-4.0wt%, Ni 0.3-0.6wt%, Fe 0.8-1.5wt%, Sn 0.5-0.7wt%, Mn ≤ 0.1wt%, Al ≤ 0.1wt%, unavoidable impurity elements ≤ 0.2wt%, and the balance is Zn.

3. The low-copper and high-iron copper alloy according to claim 1 or 2, characterized in that: The content of Si as an inevitable impurity element in the alloy does not exceed 0.02 wt%.

4. The method for producing a low-copper and high-iron copper alloy according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Ingredients: Recycled brass and brass processing scraps are used as the main raw materials, and Cu source, Pb source, Ni source, Fe source, Sn source, Al source and Zn source are added; (2) The raw materials are melted to produce ingots.

5. The method for producing a low-copper and high-iron copper alloy according to claim 4, characterized in that: The recycled brass accounts for 10-30wt% of the total weight of the raw materials, and the brass processing scraps account for no less than 50wt% of the total weight of the raw materials.

6. The method for producing a low-copper and high-iron copper alloy according to claim 4 or 5, characterized in that: The Cu source is recycled copper, the Pb source is recycled lead, the Ni source is one or both of white copper recycled material and nickel-plated recycled brass material, the Fe source is one or both of copper-iron alloy and iron powder, the Sn source is one or both of tin bronze recycled material and tin-plated recycled brass material, the Al source is one or both of recycled aluminum and aluminum bronze recycled material, and the Zn source is recycled zinc.

7. The method for producing a low-copper and high-iron copper alloy according to claim 4, characterized in that: The specific melting steps are: adding the raw materials into the smelting furnace and melting them under high pressure until flame spraying, adding slag cleaning agent under low pressure after flame spraying, taking samples after stirring for pre-furnace component analysis, if the components are unqualified, adjusting the components to qualified, removing the slag and discharging it into the casting furnace.

8. The method for producing a low-copper and high-iron copper alloy according to claim 4 or 7, characterized in that: Ingots are produced by horizontal continuous casting.

9. The method for producing a low-copper and high-iron copper alloy according to claim 4, characterized in that: The ingots are cut into extrusion billets and extruded at 600-680 °C to obtain rods with a diameter of 6-15 mm.